An integrated transcriptomic and metabolomic analysis of black spot disease in Jinggang honey pomelo reveals underlying resistance mechanisms - Sun, Huimin; Li, Weiwei; Lu, Lin; Jin, Biling; Liu, Dingkun; Li, Zexia; He, Li; Wu, Yang (Frontiers in Microbiology, 2025)
IntroductionThe Jinggang honey pomelo is recognized as one of the three major fruit industry brands in Jiangxi Province. However, the crop's growth and yield have been significantly affected by the black spot disease caused by Diaporthe citri. Despite this impact, the defense mechanisms and underlying molecular responses of the Jinggang honey pomelo to the disease remain poorly understood.MethodsIn this study, we utilized UPLC-MS/MS and RNA-Seq to conduct a comparative analysis of differentially abundant metabolites (DAMs) and differentially expressed genes (DEGs) in uninfected and D. citri-infected Jinggang honey pomelo fruits 13 days post-infection (dpi) in vivo.ResultsOur analysis yielded 1,744, 1,616, and 1,325 DAMs, as well as 3,403, 1,767, and 453 DEGs from the respective varieties, with 426 DAMs and 66 DEGs common across all three. Kyoto Encyclopedia of Genes and Genomes enrichment analysis demonstrated significant enrichment of these DAMs and DEGs in phenylpropanoid and flavonoid biosynthesis pathways. We also discovered that transcription factors (TFs), specifically MYB and bHLH, related to these pathways, were highly expressed. Our elucidation of the phenylpropanoid and flavonoid biosynthesis pathways surmises that genes (4CL, F5H, HCT, CCR, and CAD) and metabolites (p-coumaryl acetate, pinocembrin, naringin, and neohesperidin) could significantly contribute to the resistivity of Jinggang honey pomelo against D. citri.DiscussionOur findings suggest that Jinggang honey pomelo activates phenylpropanoid and flavonoid biosynthesis pathways, leading to the accumulation of flavonoid compounds that resist D. citri invasion. This study lays the groundwork for further research into the molecular mechanisms and breeding of Jinggang honey pomelo resistant to black spot disease.